ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERMASALAH DI MASA PANDEMI COVID-19 : Studi Kasus BTN Syariah KCS Bekasi - Velia Dwi Yulianti; Trisiladi Supriyanto; Mira Rahmi (2021)
This study aims to analyze and prove the effect of monitoring financing, business conditions, customer character, guarantees and the covid-19 pandemic on non-performing financing at BTN Syariah KCS Bekasi. The population of this study is customers who have problematic financing at BTN Syariah KCS Bekasi. The sampling technique in this study is the Simple Random Sampling method. In this study, the source of the data obtained was the distribution of questionnaires by obtaining 127 respondents. The data analysis technique used is the SmartPLS 3.0 tool. The results obtained from this study are Financing Monitoring (X1) has a significant effect on non-performing financing, Business Conditions (X2) has no significant effect on non-performing financing, Customer Character (X3) has no significant effect on non-performing financing, Guarantee (X4) has no significant effect on non-performing financing, and the Covid-19 (X5) pandemic had a significant effect on non-performing financing.